شعرية العنوان و العتبات المرافقة - ميراوي, عبد الوهاب; مختاري, زهرة (جامعة الوادي - University of Eloued, 2022)
العنوان من الأمور المحدثة التي اهتم بها النقّاد و الشعراء العرب المعاصرون بل من النقاّد من يعتبره مرسلة مستقلة عن العمل المعنون ، و قد جاء اهتمامنا بالعنوان نظرا لما يصنعه من مفارقات في تلقي النّص الشّعري ، فحاولنا من خلال هذه الدراسة التأكيد على ضرورة الاهتمام بالأبعاد الشّعريّة التّي تصنع من العنوان نصًّا مستقلاًّ بذاته من جهة، وكذا إمكانية تعالق هذا العنوان مع نصوص مجاورة تعرف بالعتبات النصيّة من جهة أخرى. وقد ختمنا هذه الدراسة بمجموعة نتائج تتعلّق بمدى ضرورة الاهتمام بالعتبات المرافقة باعتبارها روافد إبداعية تساهم في بناء الدّلالة العامّة و بلوغ مراتب التأويل، متوسلين في بحثنا آليتي : الوصف و التحليل. The title is one of the updated matters that contemporary Arab critics and poets have been interested in. Rather, some critics consider it an independent dispatcher of the titled work. This is what drew our interest to the title and what it makes of paradoxes in receiving the poetic text. In this research, we aimed at emphasizing the need of paying attention to poetic dimensions which makes the title an independent text on the one hand as well as the possibility of this title being related to neighboring texts known as textual thresholds. We concluded this study with a set of results related to the extent of the necessity to pay attention to the accompanying thresholds as they are creative tributaries that contribute to building general significance and achieving levels of interpretation, using the following mechanisms in our research: description and analysis.
مقال
Keywords: المناص ; العتبات النصية ; العنوان ; السيميولو جيا